Sturm intersection theory for periodic Jacobi matrices and linear Hamiltonian systems - Schulz-Baldes, Hermann (Linear Algebra and Its Applications, 2012)
Sturm-Liouville oscillation theory for periodic Jacobi operators with matrix entries is discussed and illustrated. The proof simplifies and clarifies the use of intersection theory of Bott, Maslov and Conley-Zehnder. It is shown that the eigenvalue problem for linear Hamiltonian systems can be dealt with by the same approach. © 2011 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.nat.dma.pma22.sturmi
Keywords: Bott-Maslov index; Sturm-Liouville oscillation theory